Fun with Code, Tests, and Verification - Leino, Rustan (Caltech, Pasadena, CA, 2009)
Software engineering research Goal Better build, maintain, and understand programs How do we do it? Specifications Tools, tools, tools Program semantics Verification-condition generation, symbolic execution, model checking, abstract interpretation, fuzzing, test generation Satisfiability Modulo Theories (SMT)